2018
DOI: 10.5194/amt-11-6231-2018
|View full text |Cite
|
Sign up to set email alerts
|

The Fifth International Workshop on Ice Nucleation phase 2 (FIN-02): laboratory intercomparison of ice nucleation measurements

Abstract: Abstract. The second phase of the Fifth International Ice Nucleation Workshop (FIN-02) involved the gathering of a large number of researchers at the Karlsruhe Institute of Technology's Aerosol Interactions and Dynamics of the Atmosphere (AIDA) facility to promote characterization and understanding of ice nucleation measurements made by a variety of methods used worldwide. Compared to the previous workshop in 2007, participation was doubled, reflecting a vibrant research area. Experimental methods involved sam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
130
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(141 citation statements)
references
References 71 publications
(75 reference statements)
9
130
0
2
Order By: Relevance
“…The INAS density showed a similar pattern and was found to increase with increase in particle diameter, as illustrated in Figure b. Recently, DeMott et al () showed an intercomparison of cold‐stage measurements, which includes the instrument used here. Samples included several dusts and biological particles sampled at a single location followed by distribution of the samples to different investigators.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The INAS density showed a similar pattern and was found to increase with increase in particle diameter, as illustrated in Figure b. Recently, DeMott et al () showed an intercomparison of cold‐stage measurements, which includes the instrument used here. Samples included several dusts and biological particles sampled at a single location followed by distribution of the samples to different investigators.…”
Section: Resultssupporting
confidence: 59%
“…In addition to the arguments listed in Petters and Wright, additional evidence pointing to relatively small errors emerged in the literature. Coldstage methods, including the instrument used here, agree within an order of magnitude with continuous flow diffusion chamber measurements that freeze droplets containing a single INP instead of a particle ensemble (DeMott et al, 2017(DeMott et al, , 2018. The upper bound of the gray-shaded area derived from precipitation data is consistent with continuous flow diffusion chamber measurements of INP in air over an agricultural field taken by Garcia et al (2012).…”
Section: Immersion Mode Inp Experiments Of Precipitation Samplessupporting
confidence: 66%
See 1 more Smart Citation
“…The second ice nucleation measuring system was the cylindrical continuous flow diffusion chamber INKA (DeMott et al, 2018; Schiebel, 2017). Here, the crystallized aerosol particles sampled from the AIDA chamber are constrained with particle‐free sheath flows between two cylindrical, ice‐coated walls that are controlled to different temperatures and define the temperature and ice saturation ratio at the center of the sample air flow.…”
Section: Methodsmentioning
confidence: 99%
“…Mineral dust has been inferred to be an effective INP in the atmosphere from field, model and laboratory studies Vergara-Temprado et al, 2017). Observations of aerosol within ice crystals have shown that mineral dust is often present, suggesting they act as INPs within mixed-phase clouds (Iwata and Matsuki, 2018;Eriksen Hammer et al, 2018;Pratt et al, 2009). Laboratory studies also demonstrate that mineral dusts are relatively effective at nucleating ice Murray et al, 2012;DeMott et al, 2015).…”
Section: Introductionmentioning
confidence: 99%